The training effects of wearable resistance on throwing performance in collegiate baseball pitchers: a pilot study - Job, T. D. W. III; Cross, M. R.; Cronin, J. B. (International Journal of Sports Physiology and Performance, 2025)
Purpose: The objective of this study was to explore the effects of training using wearable resistance (WR) applied above the elbow of the throwing arm on throwing velocity, arm speed, shoulder internal and external rotation, strength, and range of motion in baseball pitchers.